Orbital Subperiosteal Hematoma in the Newborn Causing Unilateral Proptosis: Ultrasound as First-Line Imaging Modality - Florencia Angkasa; Leila Mohammadi; Deepa Taranath; Ajay Taranath; Marcus Brecht (Thieme Medical Publishers, Inc., 2017)
Abstract Proptosis in the neonatal period is relatively infrequent and has diverse underlying etiologies. One of the more common causes appears to be orbital subperiosteal hematoma. Early detection, differentiation from other causes, and regular follow-up are essential as loss of vision can occur. We describe two cases of neonatal proptosis caused by orbital subperiosteal hematoma highlighting different diagnostic and management approaches, and provide a summary of previously reported cases. Spontaneous resolution occurs in most cases; however, emergent surgical evacuation is warranted in cases of optic nerve compression. This is the first report to provide orbital ultrasound images of uncomplicated neonatal orbital subperiosteal hematoma. Orbital ultrasound followed by magnetic resonance imaging (MRI) is a valid nonradiation approach for assessing neonatal proptosis due to subperiosteal orbital hematoma.